Різні форми імпліцитного у міжперсональному спілкуванні на матеріалі одно- і різноструктурних мов (української, польської, англійської) - Гнатюк, Любомира Ярославівна; Hnatiuk, L. Ya. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті розглянуто вияв різних форм імпліцитного на фактичному матеріалі української, польської, англійської мов. Досліджуються опосередковані іллокуції як лінгвістичне явище в структурі прагматики міжперсонального спілкування, зокрема в умовах міжкультурної комунікації, тому що вияв етноспецифіки застосування комунікативної стратегії натяку є також важливою умовою ефективної міжперсональної взаємодії. Розмежовуються глузування, сарказм та іронія як різні форми опосередкованого спілкування. The article is focused on the indirectness as the strategy of interpersonal communication and on the role of indirect communicative tactics in the hinting strategy in order to achieve the desirable perlocutionary effect. Linguistics of the last decades demonstrates the deep interest to the hinting strategies of interlocutors’ speech behaviour. In the article the pragmatic tactics of hinting strategies are analysed in the conditions of interpersonal communication on the material of Ukrainian, Polish, English languages. Indirect illocutions are investigated as the linguistic phenomenon in the pragmatic aspect, by the way, in the conditions of intercultural cooperation. Some specific national and cultural features are analysed. Different forms of indirectness are differentiated. The attention is paid to the ironical utterances in comparison with another implicit forms like sarcasm or mockery.
Different Forms of Implicitness in the Conditions of Interpersonal Communication on the Material of Related and Non-Related Languages (Ukrainian, Polish, English)
Keywords: стратегія натяку; indirect speech strategy; іронія; irony; прагматична імплікатура; pragmatic implicature